Studies Of Copper-Impregnated Activated Carbon For Cyanide Removal [TD758.5.C93 S525 2007 f rb]. - Saad, Shahrizam (2007)
In the present work, two types of locally manufactured granular activated carbon from Kekwa Industry (KI66G and P1814G) and Versatec Industry carbon (A, C and H) were used to study their cyanide adsorption capacity.